Increasing the efficiency of shooting of ground based air defence due to his learning - Lytovchenko, D.; Kovalenko, S. (National Academy of the National Guard of Ukraine, 2022)
Based on the results of the competitions, we can conclude that the coherence of the crew affects tAAMS . Therefore, in real aircraft combat, the effectiveness of unit firing (AAMS) will be higher in a more prepared (trained) and coordinated crew. Such a crew in a duel with the air enemy will be the first to hit (destroy) the target and emerge victorious.
Keywords: combat mission; efficiency of shooting; ground based air defence; training of the personnel